KEBIJAKAN KHARAJ DALAM PERSPEKTIF ISLAM SEBAGAI SOLUSI PENDUKUNG PEMBANGUNAN DI INDONESIA - Andika Isma; Fatimah Zahra; M. Ilham Nur; Hermaliah Hasanah Putri (Universitas Negeri Makassar, 2023)
Referring to the State Revenue and Expenditure Budget (APBN), one of the sources of state revenue is tax revenue. This tax as a supporter of cash funds in the state. However, the allocated funds are still far from sufficient. As an agrarian country, Indonesia has good potential in increasing state revenue through tax revenue through the agricultural sector by using the concept of kharaj that existed at the time of the Prophet Muhammad SAW after the conquest of the land of Khaibar. The research method used in this research is literature review, which is a study that collects scientific articles that are relevant to the research problem. The results of the study show that the concept of kharaj at the time of the Prophet was the forerunner of the provisions regarding tax collection that are still valid today. And if implemented until now, it can increase state treasury income. These cash funds can be used to increase Indonesia's development and ensure people's welfare. The tax collection method that applies in Indonesia is muqasamah which is a substitute for the wazifah method in the kharaj concept.Keywords : art criticism, evaluation, textbook